Persepsi mahasiswa terkait kemampuan mendirikan usaha di Sukabumi - Amelia Pitriyani; Dinda Nur Annisa (University of Merdeka Malang, 2023)
The small number of SMEs is caused by untrained human resources. In order for SMEs to develop, human resources must also be qualified. Therefore, SMEs owners and workers must have managerial skills, abilities and knowledge. This study begins with a general theoretical framework on perceptions, SMEs and employment factors. The purpose of this study was to determine student perceptions about the ability to establish SMEs in Sukabumi and also to determine the positive impact of the SMEs sector both in the short and long term. This study uses a descriptive qualitative approach. The subjects of this study were students from the Wiyata Indonesia Institute of Management, Muhammadiyah University of Sukabumi, Nusa Putra University and Sukabumi Open University. The results showed that students' perceptions of SMEs were better than large companies in terms of quality and management relationships, authority and participation in decision making. College graduates have the potential to become suitable and valuable resources for the development of SMEs.